1985
DOI: 10.1200/jco.1985.3.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of three combinations of cisplatin with vindesine and/or VP-16-213 in the treatment of advanced non-small-cell lung cancer.

Abstract: One hundred sixty-seven evaluable patients with non-small-cell lung cancer were randomized to receive high-dose cisplatin and vindesine (PVD), or cisplatin and VP-16-213 (etoposide epipodophyllotoxin) (PVP), or cisplatin with VP-16-213 and vindesine (PVPVD). The patient distribution and characteristics were similar in all the treatment arms. The response rate differences (35% in PVD arm, 30% in PVP arm, and 22% in PVPVD arm) were not statistically significant (P = .33). Response durations were 43 weeks in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…Although radiotherapy is of palliative value, individual cytotoxic agents have only produced low objective response rates and those responses reported have been of short duration (Hoffman et al, 1983). During the past 20 years combination chemotherapy has been extensively tested in randomised multicentre and single institution studies though almost always without a no treatment control (Simes, 1985;Dhingra et al, 1985). In general, studies comparing different combinations have yielded relatively low response rates and very similar patterns of survival regardless of therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although radiotherapy is of palliative value, individual cytotoxic agents have only produced low objective response rates and those responses reported have been of short duration (Hoffman et al, 1983). During the past 20 years combination chemotherapy has been extensively tested in randomised multicentre and single institution studies though almost always without a no treatment control (Simes, 1985;Dhingra et al, 1985). In general, studies comparing different combinations have yielded relatively low response rates and very similar patterns of survival regardless of therapy.…”
mentioning
confidence: 99%
“…In general, studies comparing different combinations have yielded relatively low response rates and very similar patterns of survival regardless of therapy. During the past decade the introduction of more intensive chemotherapy, often based on cisplatin, has resulted in an apparent small improvement in survival and a modest increase in response to therapy, but at the expense of greater toxicity (Dhingra, 1985;Klastersky & Sculier, 1985). High dose cisplatin regimes were introduced following the randomised study in which Gralla et al (1981) demonstrated that a dose of 120 mg m-2 every 4 weeks was superior to a dose of 60 mg m-2 in the same schedule.…”
mentioning
confidence: 99%
“…44 Although CIS-based chemotherapy is considered a standard treatment for advanced NSCLC, CIS has been consistently associated with marked toxicity in several epidemiological studies. 45,46 In contrast, phenolic compounds present in the human diet have been used to doses of SQE (100 ”g/mL) and CIS (0.3 ”g/mL), individually and in combination. The second and the third passages in the absent of treatment were derived from treated primary spheres.…”
Section: Discussionmentioning
confidence: 99%
“…and vindesine (3 mg m-2 i.v.) on day 1, followed by a 3 day continuous infusion of 5-fluorouracil (800 mg m-2 day-') starting on al., 1984;Dhingra et al, 1985; Kawahara et al, 1991). Treatment regimens in which one further active chemotherapeutic agent has been added to vinca alkaloid and cisplatin have been tried in an attempt to improve response and survival rates.…”
mentioning
confidence: 99%
“…Response rates of approximately 30% have since been shown in advanced NSCLC using a combination of VDS + CDDP (VP) (Elliott et al, 1984;Dhingra et al, 1985;Kawahara et al, 1991). Treatment regimens in which one further active chemotherapeutic agent has been added to vinca alkaloid and cisplatin have been tried in an attempt to improve response and survival rates.…”
mentioning
confidence: 99%